1999
DOI: 10.1163/156856299x00153
|View full text |Cite
|
Sign up to set email alerts
|

Transient adhesion of platelets in pump-oxygenator systems: influence of SMA and nitric oxide treatments

Abstract: We employed gamma scintigraphy to quantify the transient accumulations of platelets in pump-oxygenator systems employed in cardiopulmonary bypass (CPB). A flat sheet microporous polypropylene membrane oxygenator (Cobe Duo) was employed, with and without siloxane/caprolactone oligomer coating (SMA) (n = 8 each). The effect of nitric oxide gas infusion on platelet deposition was also evaluated for the uncoated Cobe Duo system (n = 10 each). Scintigraphic images of radiolabelled cells were obtained and converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Surprisingly, platelet numbers rose at the end of the 2 h recirculation procedure in the uncoated system, suggesting that surface‐bound platelets were released back into the circulating blood. Similar results have been reported in a noninvasive gamma imaging study of platelet and PMN adhesion to pump‐oxygenator circuit surfaces in a pig normothermic ex vivo perfusion model 33. We could not observe this effect in the bioactive or biopassive coated systems (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, platelet numbers rose at the end of the 2 h recirculation procedure in the uncoated system, suggesting that surface‐bound platelets were released back into the circulating blood. Similar results have been reported in a noninvasive gamma imaging study of platelet and PMN adhesion to pump‐oxygenator circuit surfaces in a pig normothermic ex vivo perfusion model 33. We could not observe this effect in the bioactive or biopassive coated systems (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…SMA biomaterial treatment has been shown to enhance blood biocompatibility in vitro and in vivo [11,13,14]. Mainly, this effect is based on reduced antithrombogenicity, thus limiting plateletsurface interaction and subsequent platelet activation [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…This technique consists of blending the SMA copolymers polycaprolactone (PCL) and polydimethylsiloxane (PDMS) with base polymer resins prior to processing at high temperature [12,13]. During processing, PCL and PDMS migrate to the polymer surface resulting in a PCL-PDMS-PCL triblock-copolymer layer of approximately 180 nm thickness, which has been shown to reduce platelet and leukocyte activation in vitro and in vivo [11,13,14]. Recently, two clinical studies by Gu et al [15] and Rubens et al [16] have shown that SMA preparation attenuates platelet-CPB circuit interaction and decreases both fibrinolysis and thrombin formation compared to untreated circuits.…”
mentioning
confidence: 99%
“…Although great efforts have been made to improve the biocompatibility of oxygenator circuits [ 3 ], serious side effects occur due to contact of blood with the artificial polymer surfaces. These side effects ultimately include reduced platelet function and survival as well as prolonged bleeding times after perfusion [ 4 ]. Consequently, the optimization of oxygenators aims for increasing gas exchange efficiency while reducing the membrane surface and blood priming volume [ 5 ].…”
Section: Introductionmentioning
confidence: 99%